1992
DOI: 10.1128/jvi.66.1.1-5.1992
|View full text |Cite
|
Sign up to set email alerts
|

UV activation of human immunodeficiency virus gene expression in transgenic mice

Abstract: Human immunodeficiency virus (HIV) infection is associated with a clinical latency of as long as 10 years before the development of disease. One explanation for this delay is the requirement of cofactors such as other DNA or RNA viruses, cytokines critical for immune modulation, or environmental UV light. At least in tissue culture studies, these agents are capable of inducing HIV gene expression in cell lines which either harbor the entire viral genome or contain a reporter gene under the control of the viral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(9 citation statements)
references
References 39 publications
(50 reference statements)
1
8
0
Order By: Relevance
“…No effect was detected after UVA irradiation. Similar results were noted by Vogel et al (14), who showed that UVC, UVB and natural sunlight could induce HIV gene expression in transgenic mice carrying both HIV-LTR and the tat gene.…”
Section: Animal Studiessupporting
confidence: 88%
“…No effect was detected after UVA irradiation. Similar results were noted by Vogel et al (14), who showed that UVC, UVB and natural sunlight could induce HIV gene expression in transgenic mice carrying both HIV-LTR and the tat gene.…”
Section: Animal Studiessupporting
confidence: 88%
“…Concern about a detrimental relationship between ultraviolet radiation and HIV infection was triggered by cell culture (1)(2)(3)(4)(5)(6) and transgenic animal studies (7)(8)(9) that have shown ul- ¶Posted on the website on 17 traviolet B (UVB), ultraviolet C and psoralens plus ultraviolet A (PUVA) treatments to upregulate HIV gene expression, activate latent HIV or promote HIV replication (or all of them). Alerted by these findings, clinical investigators studied serial cases of HIV-infected patients treated for psoriasis, eosinophilic folliculitis or pruritus, with either UVB phototherapy or PUVA photochemotherapy (10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the clearest evidence at hand, the dogmatic among us would say it is not safe. As cited, UVB and PUVA can activate HIV in vitro and in transgenic animals (5)(6)(7)(8)(9)(10)(11)(12). U1traviolet B can inhibit the immunological presentation of new antigens including components of infectious agents (3,16,17).…”
Section: Discussionmentioning
confidence: 99%
“…Support for the contention that UV radiation exerts deleterious effects on HIV infection derives principally from in vitro and transgenic animal experiments in which HIV markers were induced or upregulated (5)(6)(7)(8)(9)(10)(11)(12). These observations have led to the hypothesis that UV-induced cellular DNA damage stimulates DNA repair mechanisms, which, in turn, can activate transcription and replication of HIV (7).…”
Section: Laboratory Studies On Uv Radiation and Hiv Infectionmentioning
confidence: 99%
See 1 more Smart Citation